The Passage of Years: Not a Matter of Covert Retrieval of Autobiographical Memories - Kosak, Ferdinand; Hilbert, Sven (Frontiers in Psychology, 2021)
In current research variations in retrospective passage of time judgments for long intervals are commonly attributed to different levels of experiences in and/or accessible memories from the respective periods. This often seems to imply the assumption of a covert retrieval, where authors presume that memories from the respective interval operate on the experience of time, without these memories being somehow explicitly activated when judging. However, no studies have systematically investigated the relation between the experience of time and the regarding experiences and memories. To this end, we analysed data from three studies, where participants judged the passage of the last five years before either being asked to select outstanding life events from a list (studies 1a and b; N = 293 and 263) or recalling as many meaningful personal memories as were spontaneously accessible (study 2; N = 262). Despite applying a statistically powerful trial-by-trial mixed-effects modeling approach, in neither one of the separate datasets nor in the combined dataset, passage of time judgments can be predicted by the number of events or memories reported. This suggests that people’s spontaneous judgments of the passage of multiannual intervals, are not necessarily influenced by a covert retrieval of memories from the respective period.